2011
DOI: 10.1111/j.1463-1318.2009.02101.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic colorectal surgery - why would you not want to have it and, more importantly, not be trained in it? A consecutive series of 500 elective resections with anastomoses

Abstract: This unselected cohort of patients (the largest single surgeon series in the UK) demonstrates that in trained hands low conversion and complication rates can be consistently achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…In our study, the morbidity rate after laparoscopic re-resection was similar to that reported after both open and laparoscopic primary ileocaecal resection [6,9]. However, a conversion from laparoscopic to open surgery was observed in 8.5% of patients (6.6% for recurrent resection), which is twice the rate expected in patients undergoing laparoscopic segmental colorectal resection for other indications [25], demonstrating the complexity of these procedures. Conversion is invariably required to carry out a stricturoplasty or to mobilize a densely adherent and severely fibrotic mesentery.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our study, the morbidity rate after laparoscopic re-resection was similar to that reported after both open and laparoscopic primary ileocaecal resection [6,9]. However, a conversion from laparoscopic to open surgery was observed in 8.5% of patients (6.6% for recurrent resection), which is twice the rate expected in patients undergoing laparoscopic segmental colorectal resection for other indications [25], demonstrating the complexity of these procedures. Conversion is invariably required to carry out a stricturoplasty or to mobilize a densely adherent and severely fibrotic mesentery.…”
Section: Discussionsupporting
confidence: 85%
“…In this series, we have, like others [23,25,27,28], shown that the anticipated benefits of laparoscopy are not only seen following primary resection for Crohn's disease [1][2][3] but also for resection for recurrent disease. This was not so in the study of Brouquet et al [20], who reported a median hospital stay of 9 days for both open and laparoscopic revisional surgery, and complication rates of 15% and 10% respectively.…”
Section: Discussionsupporting
confidence: 51%
“…Our median operative times for SILS resections are comparable to those of our laparoscopic practice [52] . Data for our fi rst 100 SILS colorectal procedures includes a median of 65 minutes for anterior resection (37 -180 min), subtotal colectomy 152 minutes (58195 min), right hemicolectomy 55 minutes (17 -110 min), and TME (low anterior resection) 115 minutes (55 -280 min).…”
Section: Single -P Ort L Aparoscopic C Olorectal S Urgerysupporting
confidence: 54%
“…However, the procedure is difficult and technically demanding and requires lots of concentration. The secret of SILS lies in learning three-port laparoscopic surgery first [21].…”
Section: Discussionmentioning
confidence: 99%